Delivery of HIV test results, post‐test discussion and referral in health care settings: a review of guidance for European countries. Issue 10 (24th June 2015) - Bell, SA; Delpech, V; Casabona, J; Tsereteli, N; de Wit, J
<x xml:space="preserve">Abstract</x> Objectives HIV testing and counselling (HTC) guidelines support and promote best practice among service providers. Few European countries have national HTC guidelines and most rely on guidance from regional and international bodies. This study examines recommendations in current pan‐European and global guidelines regarding test result delivery, post‐test discussion and referral pathways in health care settings, and reviews the types of evidence upon which recommendations are based. Methods A systematic review and comparative content analysis of relevant guidelines identified through a literature search and review of targeted organization websites were carried out. Results One global and three pan‐European guidelines were reviewed. There was general consensus that any test result should be confidential and delivered privately to a patient; positive results should be delivered in person by a health care professional; negative test results could also be delivered by telephone, text message or post. Analyses show conflicting guidance relating to the provision of post‐test counselling, and inconsistencies in referral pathways to specialist treatment for positive test results. There is limited reference to published evidence in support of recommendations. Instead there is heavy reliance on expert opinion/consultation and other previous/existing guidelines when developing guidelines. Scientific evidence, where stated, is often more than ten years old, and based predominantly on US/UK research. Conclusions While largely in agreement, current pan‐European and global HTC guidelines have inconsistencies, particularly regarding post‐test counselling and referral pathways to specialized services. Our findings highlight the need for an up‐to‐date review of more current evidence from wider European settings to support the process of expert consultation.